Moderate-intensity Exercise Training in Sole and Simultaneous Forms with Insulin Ameliorates the Experimental Type 1 Diabetes-induced Intrinsic Apoptosis in Testicular Tissue - Samadian, Zahra; Azar, Javad Tolouei; Moshari, Sana; Razi, Mazdak; Tofighi, Asghar (International Journal of Sports Medicine, 2019)
The aim of this study was to investigate the ameliorative effect of moderate-intensity exercise training in sole and simultaneous forms with insulin on experimental type 1 diabetes (T1D)-induced apoptosis. A total of 36 mature male Wistar rats were divided into six equally sized groups, including sedentary control (Con), moderate-intensity exercise training (E-sole), sedentary T1D-induced (D-sole), moderate-exercise-trained T1D-induced (DE), insulin-treated sedentary T1D-induced (DI) and exercise-trained, and insulin-treated T1D-induced (DEI) groups. The 6-week exercise training intervention was involved 30 min of moderate-intensity running on a treadmill once daily (5 days/week). Next, tubular differentiation (TDI) and spermiogenesis (SPI) indices were assessed. The Bcl-2, Bax and caspase-3 expressions were determined using RT-PCR, immunohistochemistry and western blot techniques. Finally, the TUNEL staining was used to analyze the apoptosis ratio. The moderate-intensity exercise training in the sole and when simultaneously considered with insulin (DEI) maintained testicular cellularity, up-regulated Bcl-2 expression, reduced Bax expression and ameliorated the diabetes-induced apoptosis. We failed to show remarkable alterations in caspase-3 mRNA and protein levels in the DE group versus D-sole animals. In conclusion, the moderate-intensity exercise training is able to potentially protect testicular cells from T1D-induced intrinsic apoptosis via up-regulating Bcl-2 and downregulating Bax expressions. Moreover, it amplifies the insulin-induced anti-apoptotic impacts.
Keywords: spermatogenesis; moderate-intensity exercise training; type 1 diabetes; apoptosis